Mercury Bioacumulation in Muscle Tissue of Carcarhinus dussumieri - Gh. Amini rajbar1; H. Hossein zadeh email (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1994)
The Persian Gulf and Sea of Oman boast a great diversity of cartilaginous fishes of which sharks with nearly 150 different species constitute a major part. Contamination of the fishes with various chemicals necessitates the meats produced being controlled from health and quality Points of view. In this study, mercury bioacumulation in 29 specimens of Caracarhinus dussumieri caught in the coastal waters of Bandar-e- Lengeh was tested using flameless atornic obsorption spectrophotometry. Results of the analyses on muscle tissue of the cited fish revealed the mercury level being lower than the standards (0.5 PPm) of the WHO at p‹.01 significant level. The length range was determined to be 68-90 cm in males and 67.5 -88 cm in females. Mercury level in males (n=21) was assessed to be 0.21 PPm while in females (n=18) it was 0.19 PPm. Average mercury level was estimated as 0.19 ±0.023 PPm......